ANALYSIS OF THE PROPOSED APPLICATION OF THE INSOLVENCY TEST IN THE DRAFT LAW ON BANKRUPTCY AND POSTPONEMENT OF DEBT PAYMENT OBLIGATIONS BASED ON THE LEGAL SYSTEM IN INDONESIA (Lex localis - Journal of Local Self-Government, 2025)
Insolvency Test is a method used to determine the viability of the debtor’s business that will then be used to gauge the reasonableness of the debtor to be declared bankrupt. Nowadays, the insolvency test is implemented in some countries, including the United States of America, England, and Thailand. The implementation of insolvency test in some countries then becomes the basis idea for Asosiasi Pengusaha Indonesia/Indonesian Entrepreneurs Association (APINDO) to suggest that insolvency test must be included in the draft amendment of the Bankruptcy Law of Indonesia, because APINDO believes that the requirements for declaring bankruptcy to the debtor in Indonesia are overly simple. This suggestion aligns with several academics’ opinions, saying that Indonesia needs to implement an insolvency test. The insolvency test is an interesting topic to be researched, considering that Indonesia has a different understanding of concepts related to insolvency and bankruptcy because Indonesia does not recognize the insolvency test. However, in practice, fulfilling the evidence in the insolvency test related to the financial statements of the debtor (especially for corporate debtors), valuation of assets and non-performing assets is not easy and tends to be more unreliable.